Pengaruh Agregat Sungai Battang Terhadap Kekuatan Beton - Dendi Nadaf Mantja Mantja; Desi Sandy; Tjiang. A. Gunadi (Paulus Civil Engineering Journal, 2020)
The purpose of this study was to determine the aggregate characteristics and concrete strength of the Battang River material. This type of research uses the American Concrete Institute method with the identification of cylindrical specimens with a diameter of 15 cm and a height of 30 cm, a beam with a length of 60 cm, a width of 15 cm, a thickness of 15 cm. The results of the research on the plan compressive strength test 23 Mpa, amounting to 23.861 Mpa, the compressive strength plan 30 Mpa, amounting to 31.501 Mpa, the split tensile strength test with the compressive strength plan 23 Mpa is 1.957 Mpa, and the compressive strength plan 30 MPa is 2.769 Mpa, the strength test flexural compressive strength plan 23 Mpa is 3.022 Mpa, for compressive strength plan 30 Mpa is 3.425 Mpa. The aggregate characteristics of the Battang river meet the Indonesian National Standard and can achieve the planned compressive strength value.